Racial and Ethnic Disparities in Influenza Vaccination Among Elderly Adults - Rangel, María C (Blackwell Science Inc, 2005)
OBJECTIVES: To examine whether access to care factors account for racial/ethnic disparities in influenza vaccination among elderly adults in the United States. DESIGN: Indicators of access to care (predisposing, enabling, environmental/system, and health need) derived from Andersen's behavioral model were identified in the National Health Interview Survey questionnaire. The relationship of these indicators to influenza vaccination and race/ethnicity was assessed with multiple logistic regression models. MAIN RESULTS: Significant differences in vaccination were observed between non-Hispanic (NH) whites (66%) and Hispanics (50%, P<.001) and between NH whites (66%) and NH blacks (46%, P<.001). Controlling for predisposing and enabling access to care indicators, education, marital status, regular source of care, and number of doctor visits, reduced the prevalence odds ratios (POR) comparing Hispanics to non-Hispanic whites from 1.89 to 1.27. For NH blacks, controlling for access to care indicators changed the POR only from 2.24 (95% CI, 1.9 to 2.7) to 1.93 (95% CI, 1.6 to 2.4). CONCLUSIONS: This study confirmed the existence of sizable racial/ethnic differences in influenza vaccination among elderly adults. These disparities were only partially explained by differences in indicators of access to care, especially among non-Hispanic blacks for whom large disparities remained. Factors not available in the National Health Interview Survey, such as patient attitudes and provider performance, should be investigated as possible explanations for the racial/ethnic disparity in influenza vaccination among non-Hispanic blacks.